Neutrophil extracellular traps are downregulated by glucocorticosteroids in lungs in an equine model of asthma - Amandine Vargas (Respiratory Research, 2017)
Abstract Background Severe neutrophilic asthma is poorly responsive to glucocorticosteroids (GC). Neutrophil extracellular traps (NETs) within the lungs have been associated with the severity of airway obstruction and inflammation in asthma, and were found to be unaffected by GC in vitro. As IL-17 is overexpressed in neutrophilic asthma and contributes to steroid insensitivity in different cell types, we hypothesized that NETs formation in asthmatic airways would be resistant to GC through an IL-17 mediated pathway. Methods Six neutrophilic severe asthmatic horses and six healthy controls were studied while being treated with dexamethasone. Lung function, bronchoalveolar lavage fluid (BALF) cytology and NETs formation, as well as the expression of CD11b and CD13 by blood and airway neutrophils were evaluated. The expression of IL-17 and its role in NETs formation were also studied. Results Airway neutrophils from asthmatic horses, as opposed to blood neutrophils, enhanced NETs formation, which was then decreased by GC. GC also tended to decrease the expression of CD11b in blood neutrophils, but not in airway neutrophils. IL-17 mRNA was increased in BALF cells of asthmatic horses and was unaffected by GC. However, both GC and IL-17 inhibited NETs formation in vitro. Conclusion GC decreased NETs formation in vitro and also in vivo in the lungs of asthmatic horses. However, airway neutrophil activation during asthmatic inflammation was otherwise relatively insensitive to GC. The contribution of IL-17 to these responses requires further study.